OECD Principles and Guidelines for Access to Research Data from Public Funding - Dirk Pilat (Data Science Journal, 2007)
Ministers of science and technology asked the OECD in January 2004 to develop international guidelines on access to research data from public funding. The resulting Principles and Guidelines for Access to Research Data from Public Funding were recently approved by OECD governments and are discussed below. They are intended to promote data access and sharing among researchers, research institutions, and national research agencies. OECD member countries have committed to taking these principles and guidelines into account in developing their own national laws and research policies, taking account of differences in their respective national context.